Program Peningkatan dengan Subtitusi Tepung Berbahan Dasar Daun Kelor untuk Makanan Sehat di Desa Koreleko Selatan - Yadnya, Made Sutha; Wulandari, Haspita Ariana; Maryani, Indah; Zulvia, Ridho; Supiana, Wina; Hasnan P, M. Ade Zaini; Amalia3, Annisa Rizki; Devi, Radhe Vrndavanesvari; Ananda, M. Dimas; Holis, M. Sopian; Zulhidayati, Masni; Apriandi, M. Irawan (Jurnal Gema Ngabdi, 2025)
The implementation of the Village Community Empowerment (PMD) Real Work Lecture (KKN) is one of the programs that is one of the manifestations of the Tri Dharma of Higher Education, namely community service. KKN PMD is one of the educational programs that implements student knowledge outside the campus. The creative economy is a theme that is one of the sectors focusing on creativity and knowledge as the main source of added value in obtaining added value for a product. South Korleko is one of the villages located in Labuhan Haji District, East Lombok Regency. The Natural Resources (SDA) owned by South Korleko Village are quite abundant. One of them is that there are moringa gardens or trees that have not been used optimally. One of them is the use of moringa leaves as a healthy food. A good processing process can increase the value of immunity for health, so that it can become a product with a high selling value. The process of making moringa leaves into flour has been socialized and practiced to become healthy food